Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Spatial and temporal variability in δ13C and δ15N signatures of three habitat-forming kelps in the coastal upwelling system of central Chile - Sergio A. Navarrete; Eliseo Fica-Rojas; Fernanda Vargas; Ricardo Beldade; Alejandro Pérez-Matus; Evie A. Wieters (Marine Environmental Research, 2026)

Species Removal Dampens the Scale Dependency of Ecological Determinism and Stochasticity in Coastal Communities - Nelson Valdivia; Alexis M. Catalán; Daniela N. López; Moisés A. Aguilera; Claudia Betancourtt; Eliseo Fica‐Rojas; Bernardo R. Broitman (Ecology Letters, 2025)
Deterministic and stochastic processes control community dynamics. However, the responses of both processes to the loss of foundation species, which strongly influence community dynamics across spatial scales, are unclear. We experimentally examined how spatial extent and foundation species removal affect rocky‐intertidal community dynamics over 3 years in eight field sites spanning ~1000 km along the southeastern Pacific. The normalised stochasticity ratio ( NST ), which distinguishes between stochastic (> 50%) and deterministic ( NST was strongest in smaller sessile communities and diminished as spatial extent increased, while mobile communities showed no significant response to the disturbance. Our experimental results demonstrate that the loss of foundation species disrupts the scale dependency of ecological mechanisms, highlighting its negative implications for biodiversity conservation and ecosystem functioning.

Foundation species canopies affect understory beta diversity differently depending on species mobility - Alexis M. Catalán; Daniela N. López; Eliseo Fica‐Rojas; Bernardo R. Broitman; Nelson Valdivia; Ricardo A. Scrosati (Ecology, 2023)
Beta diversity measures the spatial variation in species composition. Because it influences several community attributes, studies are increasingly investigating its drivers. Spatial environmental heterogeneity is a major determinant of beta diversity, but canopy‐forming foundation species can locally modify environmental properties. We used intertidal communities dominated by the canopy‐forming alga Mazzaella laminarioides as a model system to examine how a foundation species affects spatial environmental heterogeneity and the resulting beta diversity. Since canopies were found to reduce the spatial variation of temperature and desiccation during low tides, we hypothesized that canopies would decrease understory beta diversity, which we tested through a field experiment that contrasted canopy removal with presence treatments over 32 months. The beta diversity of sessile species was always lower under canopies, but canopies never affected the beta diversity of mobile species. The observed responses for sessile species may result from their abundance being more dependent on spatial abiotic variation than for mobile species, which can occur in stressful areas while temporarily foraging or in transit to other areas. These responses may likely apply to other systems exhibiting canopy‐forming foundation species hosting sessile and mobile species assemblages.